PERBEDAAN ASSESMENT ANTARA KELOMPOK SGD MANDIRI DENGAN SGD TERBIMBING - Sri Mulyani, Sri Mulyani (Asuhan Kesehatan : Jurnal Ilmiah Ilmu Kebidanan dan Keperawatan, 2014)
One of the factors driving the achievement of learning outcomesis through the use of appropriate learning system. Learning system with Competency-Based Curriculum (CBC) is applied nation wide in 2002 (Sub-Directorate of KPS, 2008). CBC 1994 curriculum changes cause a shift towards Teacher Centered Learning concept learning (TCL) to Student Centered Learning (SCL). It drequires an active role for the achievement of student learning competencies. Some evidence suggests that the effectiveness of one of the methods of discussion in the SCL approach is the use of methods SGD to improve student learning outcomes. The purpose ofthis study is to analyze the differences Asessmen Course Community groups with SGD Self Guided Course on Application of SCL 3rd semester Student Community Diploma 3 Program Nursing Academy Rajekwesi Helath Bojonegoro. In this study,using this type of experimental research.Post test design approach that examines the influence of a group of tests on the object of research by comparing with the control group. The population in this study were  all students of the 3rd semester of  Nursing Academy Rajekwesi Health Bojonegoro, academic year 2013 / 2014, as many as112 people, while the sample number of 88 people using simple random sampling. Independent variable of this study is SGD Group Course Community. Dependent variable of this study is the Community Assessment. The results showed that the  mean value of SGD independent community group is 71.8 with a minimum value of 68.1 and a maximum value of 80, while the average value of community in the group is guided SGD 70.19 with a minimum value of 64.5 and a maximum value of 79.25. Results of independent samples t-test analysis. Obtained significance value is 0.043 is smaller than ? 0.05 so H0 is rejected, which means significant difference.Results of independent sample test showed no difference between the Community Course Asesment SGD Group Guided Self with the implementation of the semester students SCL Communities Study Diploma 3 Program Nursing Academy Rajekwesi Health Bojonegoro, academic year 2013 / 2014. Independent SGD demand in tasks students carry out in full SGD method and the total, so that he expected competencies more fulfilled. While not entirely SGD guided tasks should be done by the student. Some are still taken overby lecturer students who have actif properties during the learning process takes place. In the assessment process it was found that the average group was higher than SGD Self guided. Keywords: Asessment, SGD (Small Group Discussion) Independent, Guided, Community Subjects